SPORTS WATCHING CULTURE AMONG MALAYSIANS (International Journal of Physiotherapy, 2015)
Background: Ardent sports watching will lead an individual to engage in sports and recreational activities continuously, while it also creates a sports culture among Malaysians. Sports watching culture is actually an intellectual activity. It is capable of evaluating behaviour, moral values and the level of appreciation of every spectator.Methods: This survey was conducted to identify the sports viewing culture among Malaysians. A cluster sampling method was used to select 6000 respondents from 30 million Malaysian population. Respondents were selected from urban (50%) and rural areas (50%). Ethnically 56% were Malays, Sarawak and Sabah natives were 11%, Chinese 25% and finally Indians 7%. The respondents age categories were 12 to 19 years (30%), 20 to 25 years (50%), 56 and above (20%). A questionnaire developed by the research team was used to collect data. The quantitative data were analysed using Statistical Package for Social Sciences (SPSS) version 21.0 for windows.Results: The findings indicate that from 5864 respondents who answered the questionnaire in full, a total of 4553 people or 77.6% watch sporting events, while a total of 1311 people or 22.4% have stated not watching any sports activities. Comparison by gender showed that 85.2% of the 2482 males watch sports events while among the female 70.2% of the 2071 watch sports events. In the category of those who do not watch, the female are higher at 29.8% than the males at 14.8%. In terms of ethnicity the Malays 80.2%. Chinese 64.6%, Indians 81.9%, natives of Sabah 94.0%, natives of Sarawak 77.6% like to watch sports events. Residential locations showed no significant differences as 78.7% of urban respondents watch sports events compared to 76.8% of rural communities.Conclusion: The findings indicated that majority of Malaysians having fun in watching sports activities. Gender still plays a role in the involvement and enjoyment of sports events either as a player or supporter. Ethnicity shows some differences due to cultural, intellectual and geographical factors. Sports watching are influenced by interest, finance, facilities, comfort and privacy. The watching spirit could lead someone to involve himself/herself in sports and recreational activities continuously due to self-motivation. Viewing sport can have a positive impact on behaviour changes towards a healthy lifestyle. It will also bring progress to the sport and recreation industry. Increased level of viewing directly enhance the rate of participation and wellbeing among Malaysian.